2021
DOI: 10.1038/s41598-021-01025-8
|View full text |Cite
|
Sign up to set email alerts
|

High quality VO2 thin films synthesized from V2O5 powder for sensitive near-infrared detection

Abstract: Vapor transport method has been successfully used to synthesize high quality VO2 thin films on SiO2/Si substrate using V2O5 as a precursor in an inert-gas environment. The morphological and structural evolutions of the intermediate phases during the nucleation and growth processes were investigated by SEM and Raman spectroscopy, respectively. The results showed that the conversion of V2O5 powder to VO2 thin films was dominated by a melting-evaporation-nucleation-growth mechanism. Further characterization resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…Furthermore, the peaks at 405 and 284 cm −1 are bending vibration of the V=O (terminal oxygen) bonds, and the peaks at 304 and 481 cm −1 are bending vibrations of V 3 -O (triply coordinated oxygen) bonds and V-O-V (bridging doubly coordinated oxygen), respectively. Moreover, the peak in 700 cm −1 belongs to the asymmetric stretching of V 2 -O (doubly coordinated oxygen) bonds, and the intensity feature at 993 cm −1 belongs to the stretching vibrations of V=O (terminal oxygen) vanadyl bonds in V 2 O 5 , which is distinguished from other vanadium oxide in the Raman spectrum [ 32 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the peaks at 405 and 284 cm −1 are bending vibration of the V=O (terminal oxygen) bonds, and the peaks at 304 and 481 cm −1 are bending vibrations of V 3 -O (triply coordinated oxygen) bonds and V-O-V (bridging doubly coordinated oxygen), respectively. Moreover, the peak in 700 cm −1 belongs to the asymmetric stretching of V 2 -O (doubly coordinated oxygen) bonds, and the intensity feature at 993 cm −1 belongs to the stretching vibrations of V=O (terminal oxygen) vanadyl bonds in V 2 O 5 , which is distinguished from other vanadium oxide in the Raman spectrum [ 32 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, based on the observed processes, we found that using a larger amount of precursor causes large nuclei to form on the oxide substrate during the initial growth stage, and this advantage is maintained during subsequent growth stages, resulting in the formation of larger microplates in the complete VO 2 thin film. 20…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Furthermore, the phase transition is accompanied by rapid and ultrafast variations in resistivity and optical transmittance, particularly in the infrared range. 13–16 These excellent features of VO 2 make it a promising candidate for many practical applications, such as sensors, 17 memory devices, 18 photodetectors, 19,20 smart windows, 13 and ultrafast optical switches. 14…”
Section: Introductionmentioning
confidence: 99%
“…The multilayer structure can be feasibly fabricated using thin film deposition techniques. Growth of VO2 thin films on the order of 100nm thick have been demonstrated using RF magnetron sputtering [25] and thicker high quality VO2 films have recently been demonstrated using the vapor transport method [26]. Likewise, CaF2 films of micron thickness have been deposited using resistive evaporation [27].…”
Section: Narrowband Directional Filter Analysismentioning
confidence: 99%